Experimental study on the performance of concrete mix with paper waste, waste plastic, quarry dust, and fly ash - Gundu M.; Abhaysinha S. (Журнал інженерних наук)
In recent years, concrete in the construction industry has rapidly increased worldwide, including developing countries like India. The raw materials required to produce such a quantity require huge depletion of natural resources. On the other hand, disposal of paper waste, fly ash, and plastic waste is one of the biggest problems faced by many countries, including India, the amount of waste collected and recycled is less compared to disposal quantity. The use of these wastes in concrete reduces the disposal of waste in nature. In this experiment work, the use of these wastes in the concrete has been studied. Preliminary tests like specific gravity, fineness modulus, and water absorption have been carried out on the materials. Various mix designs are prepared by partial replacement of cement with fly ash and paper pulp, and sand is completely replaced with the quarry dust, and coarse aggregate is replaced with shredded plastic waste to create sustainable concrete. A comparative study on the properties like slump cone, the weight of the cubes, compressive strength and split tensile strength, and feasibility of such concrete has been carried out. Results indicated that the weight of cubes started to decrease with the addition of waste. Compressive strength and split tensile strength show that the strength started to fall with the addition of plastic. The cost of concrete decreased with the addition of waste. 5 % of plastic waste in concrete and 3 % of paper pulp, and 5 % of fly ash is considered the optimal replacement percentage.